Characterisation of Cassava Peel-Derived Silica at Varied Combustion Temperatures: Identifying the Optimum for Filler Applications - Bin Mohamad Fatahiyudin, Mohamad Firdaus Dzilikhram; Kamarul-Azhar Kamarudin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study looks at the possibility of using cassava peel, which is a common waste product from agriculture and industry, as a long-term source of high-purity silica by controlled burning (400–800 °C) and acid leaching. FTIR, SEM, and TGA were used to look at the structural and thermal properties of the silica that was taken out. The results showed that silica made at 600–700 °C had the best properties, such as high purity, an amorphous structure, and better thermal stability. The cassava peel-derived silica had the same physical and chemical properties as commercial silica, showing that it could be used as a cheap, environmentally friendly filler for polymers. This also shows how useful agricultural waste can be in developing sustainable materials engineering.